Evaluation of probation implementations of drug users in Adiyaman university training and research hospital: A one-year retrospective study - Mehmet Hamdi Orum; Mahmut Zabit Kara; Oguzhan Bekir Egilmez; Murat Eren Ozen; Aysun Kalenderoglu (Medicine Science, 2018)
Increasing the use of drugs all over the world and our country has become a very important social problem, making legal obligations necessary. Probation Implementation (PI) refers to the correction of the conduct of criminals causing criminal acts, the prevention of repeat offenses, the follow-up of prisoners, the rehabilitation of substance abusers, the elimination of the harm suffered by the victims, and the protection of the society in this way. In this study, it was aimed to investigate the substance use characteristics of people who applied to our hospital within the scope of PI law. 313 cases, applying to Adiyaman University, Training and Research Hospital, all of whom were decided to have PI on 01.01.2017-31.12.2017 were included in the study. PI was carried out by having psychiatric interview and evaluating psychoactive substance in urine in three-time and six-time programs. It was determined that totally 313 cases applied as required by PI during the study. These cases consist of people, 298 of whom were male and 15 of whom were female. Mean age was determined as 26.2±6.8 (15-55). It was also observed that 251 cases (80.2%) completed three-times program and 62 (19.8%) cases completed six-times program. According to the number of programs, there was no significant difference in terms of gender distribution and ethyl glucuronide positivity in two groups (p>0.05). PI, which is a fairly new practice in Turkey, has an important place in the care of substance users. In terms of gender distribution, results were consistent with studies in the literature. Alcohol comorbidities in PI-applied individuals are noteworthy. [Med-Science 2018; 7(4.000): 754-8]